OHP-029 Parents of paediatric liver transplant patients – Opinions and experiences of medicines issues. (24th February 2014) - Gutermann, L; Sharif, K; Decottignies, A; Terry, D; Rieutord, A
Abstract : Background: Immunosuppressant treatment is a critically important aspect of post-transplant patients' care. In our English paediatric hospital, a multidisciplinary team including doctors, specialist nurses and pharmacy staff is involved in family-centred care with post-transplant medicines (PTM) management. Although transplantation is perceived as a new chance of life, PTM are often felt as a constraint that can sometimes be difficult to manage. Purpose: To identify the main medicines issues encountered by children and their parents in order to find suitable means to improve their care management. Materials and methods: Anonymised multi-factorial cross-sectional survey, single-site. A questionnaire was designed to obtain parents' experiences in the 12 months prior to data collection regarding obtaining, administering and monitoring PTM, side effects (SEs) and training. A cognisance test was conducted with 4 parents and the questionnaire modified accordingly. Parents of children transplanted from January 2011 were recruited following two strategies 1- self completion during clinic attendance at the outpatient department over a period of 4 weeks during May 2013, 2- telephone completion by randomisation of 30 parents. Results: 37 parents were recruited (80.3%). Medicines supply problems (MSP) concerned 32.4% (n = 12) of parents. The main issue was that the General Practitioner declined to prescribe the medicine (s) required (35.3%). 81.1% (n = 30) of parents declared that they had almost run out of medicines but no children missed a dose because of MSP. 24.3% (n = 9) of parents experienced medicines administration problems (usually vomiting n = 7). 37.8% (n = 14) of parents were concerned by medicines-related blood test problems: obtaining the results was the main issue (n = 6). Regarding SE management, 56.6% (n = 21) of parents declared that their child had had SEs in the last year and 37.7% (n = 14) of parents felt that they had an inadequate knowledge on how to manage SEs. Concerning parents' opinions of their training, 81.1% (n = 30) of them thought that the service was excellent or very good and 97.5% (n = 36) thought that the patient support information was comprehensible and accurate. Finally, among proposed service improvements, parents' preferences were for an online learning tool (OLT) on medicines, a comic book (CB) to explain transplantation and medicine to the child, and the opportunity to have pharmaceutical consultations (PC). Conclusions: Numerous medicines-related problems were identified. However, the current multidisciplinary team seem effective in preventing children from missing doses. Due to the problems reported concerning SE management, the development of thorough information sessions for parents in this domain should be considered. Although parents seemed particularly satisfied by the current training and documentation about medicines, many experienced issues linked to PTM management. Thus, based on parents' preferences, a working party is currently considering service development options (OLT, CB, PC). No conflict of interest.